2013
DOI: 10.1016/s1995-7645(12)60201-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endostar combined with cisplatin on expression of VEGF and Sema3A of Lewis lung cancer rats

Abstract: ED combined with DDP could control the tumor growth effectively, and avoid weight loss. ED could reduce VEGF expression, and enhance Sema3A expression. Tumor vessel presents transient normalization. It is easy for DDP perfusion, and to kill tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A previous study reported that metformin decreased vascular permeability and expression of VEGF, suggesting that metformin normalizes vascular permeability by regulating VEGF levels (26). Additionally, the effects of metformin and DDP on VEGF modulation have been also described in ovarian cancer in vivo and in Lewis lung cancer rats (3,27). In the present study, metformin alone or in combination with DDP was demonstrated to significantly decrease levels of VEGF and VEGFR2 in HO-8910 cells in a concentration-dependent manner, implicating VEGF/VEGFR2 in the ERK1/2-dependent anticancer effects of metformin and DDP in ovarian cancer.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study reported that metformin decreased vascular permeability and expression of VEGF, suggesting that metformin normalizes vascular permeability by regulating VEGF levels (26). Additionally, the effects of metformin and DDP on VEGF modulation have been also described in ovarian cancer in vivo and in Lewis lung cancer rats (3,27). In the present study, metformin alone or in combination with DDP was demonstrated to significantly decrease levels of VEGF and VEGFR2 in HO-8910 cells in a concentration-dependent manner, implicating VEGF/VEGFR2 in the ERK1/2-dependent anticancer effects of metformin and DDP in ovarian cancer.…”
Section: Discussionmentioning
confidence: 93%
“…A clinical study by Masato Shingyoji also revealed that abnormal growth of lung cells in patient is because of the over-expression of VEGF [159]. Various report on anti-VEGF therapy including endostar combined with cisplatin on the expression of VEGF lewis lung cancer rats [100]. Various synthetic drugs are in clinical phase for their possible use in the treatment of lung cancer targeting VEGF and FGF-2 and their toxicity study data are mentioned in Table 3.…”
Section: Lung Cancermentioning
confidence: 99%
“…Various studies investigated the effects of anti-VEGF medication, particularly end star in combination with cisplatin, Lewis lung cancer rat's VEGF expression. [39]…”
Section: Lung Cancermentioning
confidence: 99%